The Optimization of the Potential of Digital Storytelling: A Curriculum for Teaching Creative Writing - Alwasilah, Senny Suzanna (Universitas Pasundan, 2024)
This study aims at examining the extent to which digital storytelling utilizes Storybird (a web tool for writing story) to mediate students’ learning activities. Through netnography, there are three beneficial aspects of students’ creative writing learning, which are: 1) Storybird is a platform for collaborative writing activities, 2) digital storytelling can develop students’ higher order thinking skills, and 3) digital storytelling becomes a method for implementing creative and innovative language learning. This study contributed to provide the understanding of how digital storytelling can be a learning method that provides broader thinking space for students. In addition, the purpose of this study is to invite students to participate in the process of learning creative writing.